Taking care of coexistence (Journal of Parents and Teachers, 2014)
There is a new context for school coexistence and discipline in a school, but a child is no only educated at school, parents cooperation is also required. An attention to diversity plan and a tutorial action plan are needed in order to favour student integration and participation in the school life, analyse permanently the group’s evolution and contribute to develop affective and social aspects of personality to promote growth and personal self realization.
Keywords: school mediation; attention to diversity; discipline; conflict prevention; tutorial action.